Progressive Bilateral Ptosis in Adduction Deficit: True Internuclear Ophthalmoplegia (INO) or Pseudo-INO? Poster Presentation - Case Report - Resident - MARSHA RAYFA PINTARY,; Salmarezka Dewiputri,; Annisa Nindiana Pertiwi,; Syntia Nusanti,; Sita Paramita Ayuningtyas,; Mohamad Sidik, (Ophthalmologica Indonesiana, 2024)
AbstractIntroduction : Bilateral INO is a rare disease caused by a lesion in the medial longitudinal fasciculus (MLF) in the pons, resulting in adduction deficit. Progression to ptosis is rare and may confuse with pseudo-INO as in ocular myasthenia gravis (OMG). This case aims to report progressive ptosis in bilateral INO that mimics pseudo-INO.Case Illustration : A 36-year-old woman complained sudden binocular diplopia 4 days before admission. Bilateral adduction deficits (-3 and -2 of right and left eye, respectively) with nystagmus were seen. There was no ptosis. The patient was diagnosed with bilateral INO. One month later, the patient returned with bilateral ptosis. The marginal reflex distance 1 (MRD1) were 0 on both eyes. Post fatigue and ice pack test showed 2mm difference of MRD1. The single fiber electromyography (EMG) result came out negative with jitter